KESEPIAN PADA ISTRI TENTARA NASIONAL INDONESIA - Tanti Yusnita; Ris'an Rusli; Budiman Budiman (Psikis : Jurnal Psikologi Islami, 2018)
The departure of the husband because he had to carry out the task of making the husband and wife have to live separately, this condition can be said as precipitating events that make the wife feel lonely. The purpose of the study was to find out how and the loneliness factor in the wife's stay. This research is a qualitative research phenomenon that has a meaning or concept about the experience of loneliness and influence of the wife. The results of this study found that the three research subjects experienced loneliness socially and emotionally and the factors that caused loneliness were far from their husbands, families and the environment that were not good.